Efficiency Marketing of Smoked Fish in Lingga Regency - Tetty Tetty; Haidawati Haidawati; Khairunnisa Khairunnisa; Wahyudin Wahyudin; Khairul Hafsar; Aidil Fadli Ilhamdy; Wahyu Muzammil; Septia Nurhasanah (Sangia Publishing, 2021)
Utilization of fishery in Lingga Regency is fresh fish and processed into smoked fish as we known ikan salai. The smoked Fish raw material is Fringescale sardinella (Sardinella Fimbriata). Specifically, this research is to know : (1) the marketing distribution channel of smoked fish in Lingga Regency, (2) the marketing efficiency of smoked fish in Lingga Regency. The research was conducted in September - December 2021. In the Lanjut, Berindat, Persing, and sedamai village, Singkep Pesisir District, Lingga Regency. The results of the study show is there are 2 marketing channels . Marketing channel 1, the margin amount is Rp. Rp28,462, fishery share is 34,62% and marketing efficiency is 0,57%. Marketing channel 2, the margin amount is Rp 13,750, fishery share is 75, 42%, and marketing efficiency is 0,74%. The value of marketing efficiency is 0.57% and 0.74%. The marketing channels of smoked fish in this area is efficient.